RELEVANSI BUKU KIKIGAKI MENDENGAR DAN MENULIS PADA METODE PEMBELAJARAN IPS (STUDI PUSTAKA BUKU "KIKIGAKI MENDENGAR DAN MENULIS MENJEMBATANI MANUSIA,ALAM, DAN BUDAYA KARYA KYOZON-NO-MORI NETWORK") - Wisnu Ramdan, - (2020)
One of the obstacles in achieving social studies learning objectives is the learning method in social studies learning itself. Learning methods have been widely discussed in previous studies, however. What escapes attention in social studies learning is how social studies learning achieves its goals in the appropriate learning process expected in character education. This is a problem in itself in social studies learning so that learning becomes effective and gets meaningful learning "meaningful learning". Based on these problems, it is necessary to find the right solution to improve the learning process. One of them is by applying more creative, active and innovative learning methods so that students are motivated in learning which can help students to understand the material and make students participate in the learning process. In learning, there are various learning methods available so that learning is more effective and on target. One method that teachers can apply is the "kikigaki" method, with this method students can process data and get direct experience of how social life starts from social life, culture, to the local wisdom of the community. One of the books that discusses the kikigaki learning method is a book published by The Toyota Environmental Activities Grant Program. As is well known, Japan is a country that is successful in implementing character education. In this study, the researcher used a type of library research with descriptive qualitative research methods. In the book studied by this author, he explains in detail about the kikigaki method and how the stages in the process of practicing kikigaki take place. This method can be an alternative method of choice for teachers in learning because with this method students will get new experiences on how to see the diversity of Indonesian people and their culture so that a sense of tolerance arises in students. Which will result in mutual respect and empathy behavior. This is in accordance with the objectives of social studies learning